Student-Run Free Clinic as a Source of Meaningful Ophthalmologic Care for Underserved Patients - Downie, Elaine; von Hohenberg, Maximilian; Harrison, Andrew; Sick, Brian (Journal of Student-Run Clinics, 2017)
Background: There are many student-run free clinics in existence, however few of them offer medical specialty care. Even fewer of these clinics offer eye care. Previous studies have demonstrated that ophthalmologic services are particularly difficult to access for patients who are un- or underinsured. The aim of this study was to assess community need for specialty care in an underserved neighborhood, and following implementation of these services, to evaluate the impact on our patients. Methods: Patients at a free clinic in Minneapolis were surveyed to assess demand for specialty care. After community needs were assessed, the clinic partnered with the University of Minnesota Department of Ophthalmology to establish a bimonthly ophthalmology night. Patients were then surveyed at each specialty night to determine health insurance status, reason for visiting the clinic, and satisfaction with various aspects of their clinic experience. Results: The most requested specialty was ophthalmology (34%). Following implementation, over the course of 5 clinic nights, 50 patients were seen. Of the patients surveyed, 59% did not have health insurance and 89% were satisfied or very satisfied with the clinic. Conclusions: Having adequate eye care is important for multiple aspects of patient health and well-being. Our study contributes further evidence that students in free clinics can offer important visual services to patients who would not otherwise have this access.